AJARAN DAKWAH SUNAN MURIA (KAJIAN RIJAL AL-DAKWAH) - Anasom, Anasom (Da'wa and Communication Faculty State Islamic University Walisongo, Semarang, Indonesia, 2017)
This article is an attempt to know the abouts of Sunan Muria in more depth. This is done because there are several versions of the existence of Sunan Muria from birth to death and gait da'wah that has been implemented. This article is written and extracted from the Focus Group Discussion (FGD) method that has been implemented by various universities, academics, historians and researchers who are intensive in the study of walisongo. The results of this study indicate that Sunan Muria is one son Sunan Kalijaga, the result of his marriage with the goddess Sarah binti Maulana Ishaq. In addition this article shows that the mission carried out by Sunan Muria and the condition of the people who are more embracing the religion of the earth, more precisely Kejawen community. Armed with a variety of works he made, one of the famous known pagerana omahmu kanthi mangkok (Protect Your house with bowl) makes him famous as a pious person who put forward shodaqah. It is known that sodaqah is one of the da'wah material that is often delivered